2016
DOI: 10.15244/pjoes/64325
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Carbon and Nitrogen to 15-year Experimental Warming in Two Alpine Habitats (Kobresia Meadow and Potentilla Shrubland) on the Qinghai-Tibetan Plateau

Abstract: Although the Qinghai-Tibetan Plateau (QTP) has experienced striking warming during the past century, information on how soil carbon (C) and nitrogen (N) pools of the alpine regions on the QTP respond to long-term warming is scarce. The aims of this study were to assess the response of soil organic C (SOC), total N (TN), labile C and N -including microbial biomass C (MBC) and N (MBN), inorganic N (N inorg ), dissolved organic C (DOC), and N (DON) -to 15-year experimental warming in an alpine region (Kobresia me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…One possible explanation for this result is that the cell reserves and labile substrates for microbes are depleted under warming [46]. The results of our study indicated that warming exerted no evident effect on soil TC, which is consistent with the results of Chen et al [47]. They found that 5 and 15 years of warming did not affect the SOC pool because of high soil carbon levels.…”
Section: Response Of Soil C and N Contents To Experimental Warmingsupporting
confidence: 91%
See 1 more Smart Citation
“…One possible explanation for this result is that the cell reserves and labile substrates for microbes are depleted under warming [46]. The results of our study indicated that warming exerted no evident effect on soil TC, which is consistent with the results of Chen et al [47]. They found that 5 and 15 years of warming did not affect the SOC pool because of high soil carbon levels.…”
Section: Response Of Soil C and N Contents To Experimental Warmingsupporting
confidence: 91%
“…They found that 5 and 15 years of warming did not affect the SOC pool because of high soil carbon levels. Although warming influences MBC and DOC, the proportions of these labile organic carbon (LOC) in the total SOC pool are low; thus, the variation in labile carbon is insufficient to influence the total carbon storage [47]. In addition, warming could decrease microbial decomposing capacity to recalcitrant carbon, and then ameliorate soil carbon loss [48].…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 99%
“…Decreased precipitation, however, may exacerbate warming‐induced soil drought, which would not only decrease C input, but also inhibit SOM decomposition due to increased physical protection (German & Allison, 2015; Wang, An, et al, 2021). These contrasting results are highly dependent on ecosystem types, experimental durations and edaphic characteristics (Chen et al, 2016; Ganjurjav et al, 2016). Hence, an analysis across multiple ecosystem types with heterogeneous climatic conditions is needed to adequately assess the combined effects of warming and altered precipitation on SOC at the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on soil C and N, mainly involving the effects of land use [7][8][9], management measures [10][11][12], restoration measures [13][14][15][16][17][18][19] on soil C and N, and the relationship between plant functional groups and soil factors [20][21][22]. However, most related research in China has been concentrated in the Loess Plateau area [10, 13-14, 17, 19, 22], but few studies have focused on alpine regions -especially the Sanjiangyuan region [12,18,[23][24][25]. Based on the above grassland restoration background, we investigated the changes of C and N in grassland soil under different restoration measures in the Sanjiangyuan region.…”
Section: Introductionmentioning
confidence: 99%